The use of Bamboo in construction: a sustainable alternative - Cunha, Cleysson Márcio Guimarães da; Machado, Priscila Alves da Silva (International Journal of Advanced Engineering Research and Science, 2023)
The civil construction sector, responsible for the movement of billions of reais, demonstrates a substantial economic impact in Brazil. However, this impact is accompanied by the high consumption of natural resources and the generation of waste. Faced with growing environmental awareness and the need to reduce impacts arising from this nature, interest in sustainable alternatives arises, with emphasis on bamboo, due to its remarkable resistance, characteristics and rapid growth. This work proposes to investigate the perspectives of using bamboo in construction and identify strategies for its effective adoption, considering economic, sustainable and regulatory aspects.